Can celebrity athletes burst the echo chamber bubble? The case of LeBron James and Lady Gaga. (November 2020) - Hayat, Tsahi; Galily, Yair; Samuel-Azran, Tal
This study examines the case of basketball superstar LeBron James, who openly identifies as a liberal. Our analysis of LeBron James' Twitter profile revealed normal distribution between liberals and conservatives following his account. We then compared James' followers' distribution to those of the singer Lady Gaga and liberal-tilting sport network ESPN and found that James' followers' distribution represented the most diverse distribution of the three accounts. We further found that James was the only liberal source in most of his conservative followers' profiles. The findings highlight the potency of celebrity athletes to narrow the trend of political polarization.